Imaging features of intrapancreatic accessory spleen - Spencer, L A (The British Institute of Radiology., 2010)
Although accessory spleens are commonly identified on CT, intrapancreatic accessory spleen (IPAS) is often not recognised or is mistaken for other pancreatic lesions. Currently, with improved cross-sectional techniques and spatial resolution, IPAS is more detectable. We report the imaging features and work-up for the differentiation between IPAS and other pancreatic lesions. An index case of a suspected pancreatic tail islet cell tumour, subsequently confirmed as IPAS, led to inquiries into the incidence of IPAS and the means of preventing unnecessary surgery. For 2 years, we searched for IPAS during our daily interpretations and compared these cases with those taken from our institution's database to determine the distinguishing characteristics. Three proven cases of IPAS, which mimicked pancreatic tail lesions on CT, are presented. Nine patients with suspected IPAS, based on imaging characteristics and stability, are also described. All cases of IPAS are well defined, 1–3 cm in size, follow the density and intensity of the spleen on CT and MRI, and accumulate technetium-99m ((99)Tc(m)) sulphur colloid and (99)Tc(m) heat damaged red blood cell scintigraphy (in contrast to other lesions). In conclusion, radiologists should be aware that a subtle pancreatic tail lesion could be an IPAS. A high index of suspicion will lead to correlative imaging. A combination of CT, MRI and nuclear medicine examinations can confirm the diagnosis and prevent unnecessary surgery.